Hydrothermal Dehydration of Monosaccharides Promoted by Seawater: Fundamentals on the Catalytic Role of Inorganic Salts - Kammoun, Maroua; Istasse, Thibaut; Ayeb, Haitham; Rassaa, Neila; Bettaieb, Taoufik; Richel, Aurore (Frontiers in Chemistry, 2019)
In biorefining, the conversion of carbohydrates under subcritical water conditions is a field of extensive studies. In particular, the hydrothermal decomposition of benchmark C6- and C5-monosaccharides, i.e. D-glucose and D-xylose, into furanics and/or organic acids is fully considered. Herein, we propose to establish the fundamentals of the decomposition of D-glucose and D-xylose under subcritical water conditions in the presence of specific salts (i.e. NaCl and KI) and in seawater. Our results demonstrated that the introduction of inorganic salts was found to modify sugars dehydration yields. Different NaCl concentrations from 0.21 to 1.63 mol L-1 promoted the conversion of D-xylose to 2-furfural (2-F) from 28 to 44% (molar yield). NaCl also improved 5-hydroxymethylfurfural (5-HMF) generation from D-glucose as well as rehydration of 5-HMF to levulinic and formic acid. KI favored other pathways towards formic acid production from D-glucose, reaching 20% in the upper concentration. Compared to a solution of equivalent NaCl concentration, seawater enhanced selectivity towards lactic acid which was raised by 10% for both monosaccharides, and sugars conversion, especially for D-glucose whose conversion was increased by 20%. 5-HMF molar yield around 30% were achieved from D-glucose in seawater at 211°C and 20 bars after 15 min.